2006
DOI: 10.1111/j.1472-765x.2006.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus subtilis strains in Thua nao, a traditional fermented soybean food in northern Thailand

Abstract: Aims:  To clarify the diversity of Bacillus subtilis strains in Thua nao that produce high concentrations of products useful in food manufacturing and in health‐promoting compounds. Method and Results:  Production of amylase, protease, subtilisin NAT (nattokinase), and gamma‐polyglutamic acid (PGA) by the Bacillus subtilis strains in Thua nao was measured. Productivity of protease NAT by these strains tended to be higher than by Japanese commercial natto‐producing strains. Molecular diversity of isolated strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 26 publications
3
66
0
Order By: Relevance
“…from fermented pork, fermented fish, fermented tea leaves and pickled garlic (Klayraung et al, 2008) and Bacillus sp. from fermented soybean (Thua nao) (Inatsu et al, 2006). Lactic acid bacteria, especially in the genus Lactobacillus, have been well-studied probiotics for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…from fermented pork, fermented fish, fermented tea leaves and pickled garlic (Klayraung et al, 2008) and Bacillus sp. from fermented soybean (Thua nao) (Inatsu et al, 2006). Lactic acid bacteria, especially in the genus Lactobacillus, have been well-studied probiotics for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, B. subtilis has been touted as a probiotic that when ingested has "beneficial" effects, likely by helping to maintain or restore "healthy" bacterial communities in the body 18 . B. subtilis is also found in several commercially available fermented food products, including soy beans fermented with B. subtilis natto which is popular in Japan and which has been long thought to confer health benefits 19 . But as its role in plant growth promotion, just how B. subtilis imparts its probiotic effects is not clear.…”
Section: Where Do We Find Bacillus Subtilis?mentioning
confidence: 99%
“…It was also the case for Asian fermented foods product of soybean fermentation for example, Kinema (Sarkar et al, 2002); Thua-nao (Inatsu et al, 2006). Heat resistance of B. subtilis spores has been investigated by Fox and Eder (1969) and Warth (1978), who found that the decimal reduction time at 100°C (D 100 ) was in the order of magnitude of 10 min.…”
Section: Bacteria Encountered In Tayohountamentioning
confidence: 99%